Using LEGO MINDSTORMS in Primary Schools: Perspective of Educational Sector - AlQarzaie, Khawla Nasser; Awadh AlEnezi, Sara (International Journal of Online and Biomedical Engineering (iJOE), 2022)
Programming is a great means for kids to learn different skills such as logical thinking and problem solving. LEGO MINDSTORMS This study explores the readiness and viability of teaching program-ming schools in Saudi primary schools using LEGO MINDSTORMS.LEGO MINDSTORM was chosen as it is a good tool for LEGO MINDSTORMS playing and education. This study conducted a survey to investigate the opinions of education officials and education managers toward the viability of using LEGO MINDSTORMS to teach students programming concepts in primary schools. The samples were from the ministry of education. The ministry’s members gave recommendations on how LEGO MINDSTORMS can be introduced to the primary school students and identified some of the obstacles that may delay this process. Based on the survey. The survey results showed that more than half of the members agree that primary school students should introduce programming skills. The results also showed that most of them prefer Scratch software over LEGO MINDSTORM to teach programming.Programming is a great means for kids to learn different skills such as logical thinking and problem solving. LEGO MINDSTORMS This study explores the readiness and viability of teaching program-ming schools in Saudi primary schools using LEGO MINDSTORMS.LEGO MINDSTORM was chosen as it is a good tool for LEGO MINDSTORMS playing and education. This study conducted a survey to investigate the opinions of education officials and education managers toward the viability of using LEGO MINDSTORMS to teach students programming concepts in primary schools. The samples were from the ministry of education. The ministry’s members gave recommendations on how LEGO MINDSTORMS can be introduced to the primary school students and identified some of the obstacles that may delay this process. Based on the survey. The survey results showed that more than half of the members agree that primary school students should introduce programming skills. The results also showed that most of them prefer Scratch software over LEGO MINDSTORM to teach programming.